Characterization and Potential Application of Phage vB_PmuM_CFP3 for Phage Therapy Against Avian Pasteurella multocida - Hongmei Chen; Nansong Jiang; Guanghua Fu; Qiuling Fu; Chunhe Wan; Yu Huang; Yuan Liu; Rongchang Liu; Qizhang Liang; Longfei Cheng (Animals)
The rise of antibiotic-resistant bacterial infections necessitates alternative therapeutic strategies, such as phage therapy. This study investigates the potential of phage vB_PmuM_CFP3 (CFP3) as a therapeutic agent against avian cholera caused by Pasteurella multocida (P. multocida). Phage CFP3 was isolated from the feces and wastewater of a laying hen farm and underwent comprehensive biological characterization, including host range, lytic activity, and environmental stability. Transmission electron microscopy revealed CFP3′s typical myovirus morphology, with a head diameter of approximately 60 nm and a tail length of about 120 nm. CFP3 demonstrated high stability across a pH range of 4–10 and temperatures of 30–40 °C, making it suitable for oral administration in poultry. The phage exhibited a latent period of about 90 min and an optimal multiplicity of infection (MOI) of 1. Despite its narrow host range, with a lysis rate of 28.2% against avian-derived type A P. multocida, CFP3′s specificity minimizes impact on non-target bacteria. Whole-genome sequencing revealed a 32,696 bp linear double-stranded DNA genome with 46 predicted open reading frames (ORFs) and no tRNA or antibiotic resistance genes, enhancing its safety profile. Phylogenetic analysis indicated a close evolutionary relationship with Haemophilus phages HP1, HP2, and Pasteurella phage F108. While CFP3 shows promise as a precision therapeutic tool, further in vivo studies are required to evaluate its efficacy and safety. Future research should focus on expanding the phage library, optimizing phage mixtures, and exploring synergistic effects with other antimicrobial strategies. This study provides foundational data supporting the development of CFP3 as a viable alternative to antibiotics for controlling avian cholera.